THE EFFECT OF QUIZIZZ APPLICATION ON THE STUDENTS’ READING COMPREHENSION - Niscaya Annisa; Arik Susanti (Wiralodra English Journal, 2024)
This study aims to ascertain whether using the Quizizz application affects students' reading comprehension abilities in seventh-grade junior high school. The researchers used a pre-experiment design with a single group design to conduct this quantitative study. Seventh graders at one of Surabaya's public junior high schools served as the study's sample. Pre-test and post-test were utilized in this study to gather data. This study examined a paired sample t-test to collect the information. The t-test indicates that the student's scores after receiving the treatment are higher than the students' scores before, as evidenced by the average score's increase from 64.41 to 81.12. The Alternative hypothesis is accepted as there is a substantial impact of utilizing Quizizz on students' reading comprehension abilities, according to the findings of the paired sample t-test, which revealed that the Sig (2-tailed) score is 0.000 <0.05. It has implied that Quizizz could improve students' reading comprehension since the teacher provides valuable knowledge for students.  They are motivated to read English text using Quizizz. It is recommended for future research to explore the application of Quizizz for other skills.